Analisis Aspek Transfornasi Tingkat Kreativitas Desain Produk Mahasiswa Pendidikan Fisika Dalam Pembelajaran Elektronika Analog - Prasetyo, Ponang Tri; Edie, Sukiswo Supeni (UPEJ Unnes Physics Education Journal, 2021)
In the 21st century education and technology are developing more rapidly. This requires each individual to have skills. One of the skills that must be possessed is creativity. According to Munandar creativity is devided into four models namely person, process, press and product. Product creativity according to Peter Nilsson can be assessed in terms of product form and product Quality based on theory of village Taxonomy Design Creativity Peter Nilsson product form is devided into five aspects, namely Imitation, Variation, Combination, Transformation, and New Creation. This research focuses on transformation aspects only, conducted on Physics Education college students who have received analog electronics courses, then college students are asked to design the opening and closing tools of the water tap according to the order sheet, to then be assessed with an instrument that has been validated by an expert lecturer. The data analysis technique uses a descriptive quantitative approach. The results of the data analysis concluded that the level of creativity of physics education college students in designing the product aspects of transformation, 5,1 on a scale of 0-7 which means college students of UNNES physics education have a high level of creativity.